VITALITAS BAHASA JAWA DAN BAHASA MADURA DI DESA REJOYOSO, KECAMATAN BANTUR, KABUPATEN MALANG (KAJIAN SOSIOLINGUISTIK) - Wahyuni, Rera Astri (Hasta Wiyata, 2021)
Rejoyoso Village is a village with two ethnicities, namely Javanese and Madura. Rejoyoso village was chosen as a research area by reason of the existence of bilingualism in 70% of the community. Bilingualism in question is the mastery of two regional languages as the first language and second language (Javanese and Madura). Javanese is dominant in the hamlets of Wotgalih and Balong. Madurese language is dominant in Sukosari and Karangsuko Hamlets. This research focuses on the domains which influence communication and the vitality of Javanese and Madurese languages in Rejoyoso. This research is a quantitative descriptive study using a questionnaire instrument. The research location is in Rejoyoso Village by taking samples from hamlets in Rejoyoso in accordance with the dominance of the language. The results of this study indicate that the vitality of Javanese and Madurese languages is not on a safe scale, but on a vulnerable scale (stable and stable, but endangered). The use of regional languages is low in domains such as population mobility, governance, education, transactions, bilingualism, poverty, language attitudes, and religion. The safe domains are the family domain, the neighborhood and the domain of expression.